Can the Islamic bank be an emerging leader? A panel data causality analysis. Issue 14 (21st September 2016) - Jawadi, Fredj; Idi Cheffou, Abdoulkarim; Jawadi, Nabila
ABSTRACT: This short note investigates the ability of Islamic banks (IBs) to play a leading role in revamping and driving conventional banking. To this end, we used a panel of 10 major conventional banks (CBs) and 10 IBs over the period 2006–2013. We applied panel regression tests and carried out a panel causality analysis. Our findings identified no significant causality effect from IBs to CBs and indicated that IBs are not able to play a role of leader.